2020
DOI: 10.4028/www.scientific.net/kem.833.223
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Analysis of Stiffened Cone-Cylinder Intersection Subjected to External Pressure

Abstract: This paper aims to examine the influence of ring stiffener reinforcement on the buckling behavior of cone-cylinder intersection subjected to external pressure. Three different stiffener locations were analyzed; they are (i) cone-cylinder intersection, (ii) cone mid-section, and (iii) cylinder mid-section. Internal and external stiffeners are used in the study. Buckling strength of the stiffened cone-cylinder intersections were obtained with the aid of FE analyses for all the cases above. Cone-cylinder intersec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…FE analysis was used to analyze the influence of imperfections by the eigenmode-affine method and single perturbation load approach on cylindrical shells under axial compression load for different geometries and materials, and obtained single perturbation load approach is significantly better for the preliminary design process of composite cylindrical shells [71]. Ismail et al [72] presented a numerical study on stiffened cone-cylinder intersections subjected to external pressure with three different types of stiffeners by using FE simulations ABAQUS and determined the buckling capacity of stiffened cone-cylinder intersection is more for suitable preliminary design of conecylinder. Kumar et al [73] analyzed two different types of hat-stiffened panels with variations of different parameters with the application of the Finite Element tool ABAQUS and provided a database based on a smeared stiffness approach for three different plies configurations of skin.…”
Section: Application Of Finite Element Software Based On Femmentioning
confidence: 99%
“…FE analysis was used to analyze the influence of imperfections by the eigenmode-affine method and single perturbation load approach on cylindrical shells under axial compression load for different geometries and materials, and obtained single perturbation load approach is significantly better for the preliminary design process of composite cylindrical shells [71]. Ismail et al [72] presented a numerical study on stiffened cone-cylinder intersections subjected to external pressure with three different types of stiffeners by using FE simulations ABAQUS and determined the buckling capacity of stiffened cone-cylinder intersection is more for suitable preliminary design of conecylinder. Kumar et al [73] analyzed two different types of hat-stiffened panels with variations of different parameters with the application of the Finite Element tool ABAQUS and provided a database based on a smeared stiffness approach for three different plies configurations of skin.…”
Section: Application Of Finite Element Software Based On Femmentioning
confidence: 99%
“…The numerical analysis was presented according to the ECCS (1988a) guideline which consists of (i) linear analysis (LA), (ii) geometrical nonlinear analysis (GNA) and (iii) geometrical material nonlinear analysis (GMNA). In more recent, Ismail et al (2020bIsmail et al ( , 2020aIsmail et al ( , 2018 carried out a numerical investigation into cone-cylinder transition subjected to external pressure by revisiting the work conducted by (Galletly et al, 1974). The study examined the buckling sensitivity of conecylinder intersection and the role of additional stiffener reinforcement at each section (cone/intersection/cylinder) subjected to external pressure.…”
Section: Past Findingmentioning
confidence: 99%
“…Again, it may suggest that the ring-stiffeners may be inappropriate for the larger cone angle mentioned above. Ismail et al (2020bIsmail et al ( , 2020aIsmail et al ( , 2018 reported that under external pressure, the (i) shell with stiffened intersection appeared more prominent in resisting buckling through nonlinear analysis. Although in bifurcation study, (ii) stiffened the cone part was more noticeable in producing a stronger shell.…”
Section: Summary Of Findingmentioning
confidence: 99%